PENGARUH KECAKAPAN MANAJERIAL, PENERAPAN CORPORATE GOVERNANCE, KOMPENSASI BONUS DAN LEVERAGE TERHADAP MANAJEMEN LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI 2015-2017) - Binsar Simajuntak; Lucky Amirullah Anugerah (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
The purpose of this study was to examine the effect of Managerial Skills, Corporate Governance, Bonus Compensation, Leverage on Earnings Management with Company Size as a moderating variable. Managerial ownership is measured using Confirmatory Factor Analysis, Corporate Governance is measured based on the Asean Corporate Governance Balance Scorecard, Bonus Compensation is measured by the company's dummy compensation bonus, Leverage is measured using the debt to equity ratio, Company Size is measured using Log Natura of total assets, and Profit management is measured by using the Stubben model with the Conditional revenue model proxy.Hypothesis testing is done by using multiple regression models by first performing a classic assumption test. The population and sample used in this study were 80 companies with a total of 181 observation samples of manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2017 period. The results of this study are (1) Managerial skills do not have a positive effect on earnings management (2) Corporate governance does not negatively affect earnings management (3) Bonus compensation has a positive effect on earnings management (4) Leverage has a positive effect on earnings management (5) Size company has a negative effect on earnings management (6) Company size does not weaken the positive influence of managerial skills on earnings management (7) Firm size does not weaken the negative influence of corporate governance on earnings management (8) Firm size weakens the positive effect of bonus compensation on earnings management (9) Company size weakens the positive influence of leverage on management.